The Discourse of Modern Intellectual Awareness: Quranic Perspective on the Unity of the Muslim Ummah and the Renewal of Thought (Al-Aasar, 2025)
This article argues that the perceived antagonism between “modern thinking” and Muslim unity is a historical misconception rooted in colonial and post-colonial distortions, whereas authentic modernity defined by rationality, universality, human dignity, scientific inquiry, consultative governance, and principled pluralism is indigenous to the Qur’ānic worldview and Prophetic practice. Beginning with the contemporary paradox of 57 OIC member states amid escalating disunity, it establishes tawḥīd as the ontological foundation of communal solidarity, diversity as divine intentionality rather than curse, and the explicit prohibition of tafarruq and taḍādd as categorical imperatives. The Prophetic model in Madīnah is presented as the archetype of pluralistic yet cohesive polity, transcending tribalism through faith-based brotherhood and the Farewell Sermon’s radical egalitarianism. Historical deviations, sectarian crystallisation, colonial “divide and rule” policies, and the post-colonial nation-state idolatry are analysed as successive ruptures from this original vision. Modern reformist thinkers from al-Afghani and ‘Abduh to Iqbal, Bennabi, Shariati, Mutahhari, and contemporary initiatives such as the Amman Message, Marrakesh Declaration, and Document on Human Fraternity are examined as convergent efforts to reclaim rational ijtihād and revolutionary spirituality for cross-sectarian renewal. The conclusion reinterprets ostensibly “Western” values ‘aql as a source of law, human rights through maqāṣid al-sharī‘ah, scientific temperament, shūrā as democracy, and pluralism via Millat Ibrāhīm as recovered Islamic imperatives. Ultimately, the article argues that the message of genuine modernity is not division but the restoration of a dynamic, tawḥīdic ummah capable of civilisational leadership in the twenty-first century.